In the Rainfield : who is the greatest? - Olaleye, Isaac; Grifalconi, Ann (New York : Blue Sky Press, 2000)
When Wind, Fire, and Rain meet in the land of the Yoruba to decide which of them is the greatest, Wind and Fire make great shows of strength, but Rain demonstrates the power of gentleness.
Keywords: Yoruba (African people) -- Folklore; Folklore -- Nigeria